2010
DOI: 10.1021/je100081v
|View full text |Cite
|
Sign up to set email alerts
|

Cosolvent Selection for Benzene−Cyclohexane Separation in Extractive Distillation

Abstract: The Krupp-Koppers (K-K) extractive distillation method with N-formylmorpholine (NFM) as the solvent is one of the most important processes for catalytic hydrogen refining of rude benzene. To increase the capacity and selectivity of the solvent and decrease the ratio of solvent to feed in this process, ethylene glycol (EG), N,N-dimethylformamide (DMF), and N-methylpyrrolidone (NMP) were introduced as the cosolvent with NFM. The relative volatility of cyclohexane to benzene (R) at a certain R stf (liquid-phase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…In petrochemical industries, usually ethylene glycol uses as a second solvent to form a cosolvent with NFM in extractive distillation [22]. Regarding this, in the current investigation, the CPA model was used to model the phase behavior of the system containing NFM with EG considered as a cross-associating system.…”
Section: Nfm-ethylene Glycolmentioning
confidence: 99%
See 1 more Smart Citation
“…In petrochemical industries, usually ethylene glycol uses as a second solvent to form a cosolvent with NFM in extractive distillation [22]. Regarding this, in the current investigation, the CPA model was used to model the phase behavior of the system containing NFM with EG considered as a cross-associating system.…”
Section: Nfm-ethylene Glycolmentioning
confidence: 99%
“…In this way, the experimentally measured data by Yin et al [22] and Huang et al [19] at lowpressure liquid-vapor region combined by "4C & CR1 and 2B & CR1" association schemes were used to evaluate the performance of utilized modeling approach. A close examination in the results tabulated in Table 6 (see Figs. 10 and 11) demonstrated that there is a direct relation between the deviation and temperature.…”
Section: Ternary Mixturesmentioning
confidence: 99%
“…The most common method to recover the extractive agent is rectification with another column. To keep the cost of this operation to a minimum, the feed and solvent must have an appreciable difference in their boiling points [11]. Usually, this means the boiling points must vary by 20 K [14,15].…”
Section: Single Solventsmentioning
confidence: 99%
“…In the synthesis process of DMC, methanol is used excessively as a raw material. , Under atmospheric pressure, the mixture of DMC and methanol is difficult to be separated by conventional separation methods for the formation of the homogeneous azeotrope. , Therefore, some special separation techniques need to be considered, including cryogenic crystallization, pressure swing distillation, extractive distillation, , azeotropic distillation, , membrane separation, and so forth. It has been proved that the extractive distillation is an effective method, but the selection of the entrainer is the crucial step. …”
Section: Introductionmentioning
confidence: 99%